Money and monetary policy in Communist China - Hsiao, Katharine H. Y. Huang (New York : Columbia University Press, 1971)
This book is aimed at determining the part played by money and banking in the Chinese economy. It also examine the nature of China's monetary policy and to see whether the latter has contributed toward the maintenance of economic stability.
Includes index
Includes bibliographical references: p. 277-298.
usc 24/07/2019
Loans
Keywords: Money; Monetary policy; China